Attention and Memory Biases in Social Anxiety Disorder: The Role of Comorbid Depression - LeMoult, Joelle (2010)
Cognitive biases play an important role in the onset and maintenance of Social Anxiety Disorder (SAD). Few studies, however, have examined the role of comorbid Major Depressive Disorder (MDD) in the processing of emotional material. In addition, little is known about the relation among different cognitive biases. In the current study, 73 participants (54.79% female) completed an emotion face dot-probe task followed by a recognition memory test. Compared to participants with SAD, participants with comorbid SAD and MDD oriented away from supraliminally presented angry faces. Subsequently, SAD participants with and without comorbidity recognized fewer angry faces than non-disordered controls. Furthermore, attention biases for subliminally presented stimuli predicted recognition accuracy only for comorbid participants. These results suggest that the presence of comorbid MDD affects attentional orienting in SAD participants. In addition, it highlights the interconnectedness of attention and memory biases for comorbid participants.